Institutional Profile: University of California San Diego Pharmacogenomics Education Program (PharmGenEd™™): bridging the gap between science and practice. (February 2011) - Kuo, Grace M; Ma, Joseph D; Lee, Kelly C; Halpert, James R; Bourne, Philip E; Ganiats, Theodore G; Taylor, Palmer
Clinical application of evidence-based pharmacogenomics information has the potential to help healthcare professionals provide safe and effective medication management to patients. However, there is a gap between the advances of pharmacogenomics discovery and the health professionals'' knowledge regarding pharmacogenomics testing and therapeutic uses. Furthermore, pharmacogenomics education materials for healthcare professionals have not been readily available or accessible. Pharmacogenomics Education Program (PharmGenEd™™) is an evidence-based pharmacogenomics education program developed at the University of California San Diego Skaggs School of Pharmacy and Pharmaceutical Sciences and the School of Medicine (CA, USA), with funding support from the Centers for Disease Control and Prevention. Program components include continuing education modules, train-the-trainer materials and shared curriculum modules based on therapeutic topics, and virtual communities with online resources.